TEKNIK INDIVIDUAL DEMONSTRATION INTERVIEW DALAM BAHASA DAYAK KEBAHANT UNTUK MENGGALI MISKONSEPSI TENTANG SIFAT CAHAYA - Apriani, Witri; Sitompul, Stepanus Sahala; Arsyid, Syaiful B (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is designed to explore the misconceptions of the students of SD Negeri 12 Pinoh Utara on the concepts of the nature of light. Individual Demonstration Interview (IDI) technique in Dayak Kebahant language was used to explore the misconceptions of nine elementary school students of class V. The data were analyzed qualitatively by comparing the students' conceptions and the conception of the scientist to obtain students' misconceptions. The results showed that students had misconceptions about the material nature of light. Students assumed that light could propagate straight because there was light, light could penetrate a transparent object when it was made of a thin material, when light came from a less dense medium to a closer medium away from the normal line and the sun was yellow. Students tend to express their concepts based on concrete things. The results of the research are useful in conducting the learning process. It is advisable to conduct further research in exploring students' misconceptions with appropriate methods.Keywords: Misconceptions, Individual Demonstration Interview Technique, Dayak Kebahant Language